Carbonic Anhydrase IX is Not a Predictor of Outcomes in Non-Metastatic Clear Cell Renal Cell Carcinoma - A Digital Analysis of Tissue Microarray - Zerati,Marcelo (2013)
Introduction The knowledge about the molecular biology of clear cell renal cell carcinoma (ccRCC) is evolving, and Carbonic Anhydrase type IX (CA-IX) has emerged as a potential prognostic marker in this challenging disease. However, most of the literature about CA-IX on ccRCC comes from series on metastatic cancer, with a lack of series on non-metastatic cancer. The objective is to evaluate the expression of CA-IX in a cohort of non-metastatic ccRCC, correlating with 1) overall survival, and 2) with established prognostic parameters (T stage, tumor size, Fuhrman nuclear grade, microvascular invasion and peri-renal fat invasion). Materials and Methods This is a retrospective cohort study. We evaluated 95 patients with non-metastatic clear cell renal cell carcinoma, as to the expression of CA-IX. The analyzed parameters where: overall survival (OS), TNM stage, tumor size (TS), Fuhrman nuclear grade (FNG), microvascular invasion (MVI), peri-renal fat invasion (PFI). We utilized a custom built tissue microarray, and the immunoexpression was digitally quantified using the Photoshop® software. Results: Th e mean follow-up time was 7.9 years (range 1.9 to 19.5 years). The analysis of CA-IX expression against the selected prognostic parameters showed no correlation. The results are as follows: Overall survival (p = 0.790); T stage (p = 0.179); tumor size (p = 0.143); grouped Fuhrman nuclear grade (p = 0.598); microvascular invasion (p = 0.685), and peri-renal fat invasion (p = 0.104). Conclusion Carbonic anhydrase type IX expression does not correlate with overall survival and conventional prognostic parameters in non-metastatic clear cell renal cell carcinoma.